How should a Resource Room Programme for Gifted Students be Integrated into School System? - Ercan ÖPENGİN; Hasan GÜRGÜR (Anı Publishing, 2021)
The present research aims to determine the problems encountered during the integration of a resource room for gifted students in a primary school system and examining the measures developed for dealing with these problems. Structured as an action research, this research project was conducted in a primary school in the Eskisehir province of Turkey. Participants in this research consisted of the school headmaster, the teacher of the resource room, gifted students attending the resource room, parents of gifted students and classroom teachers whose students attended the resource room, researchers and the members of the evaluation board. Data were collected using interviews, meeting reports, documents and the researcher's diary. The research data were analyzed using the systematic analysis approach. The findings of this research showed that the resource room were generally positively perceived; however, several problems were observed as the programme was carried out during regular class hours. The findings obtained in this study suggest that in order for the gifted student resource room to be efficient, it should be implemented in coordination with classroom teachers.